y=\frac{x + 8}{4} |
y=\frac{-3\cdot x + 6}{2} |
y=\frac{x + 8}{2} |
y=\frac{-x + 12}{4} |
y=\frac{-5\cdot x + 2}{2} |
y=\frac{-3\cdot x + 2}{2} |
y=\frac{5\cdot x + 6}{2} |
y=\frac{-3\cdot x + 4}{2} |
y=\frac{-5\cdot x + 8}{2} |
y=\frac{3\cdot x + 6}{2} |
y=\frac{-3\cdot x + 6}{2} |
y=\frac{-x + 2}{2} |
y=\frac{x + 8}{4} |
y=\frac{-3\cdot x + 2}{2} |
y=\frac{5\cdot x + 4}{2} |
y=\frac{5\cdot x + 12}{4} |
y=\frac{3\cdot x + 4}{4} |
y=\frac{-5\cdot x + 16}{4} |
y=\frac{3\cdot x + 8}{2} |
y=\frac{-5\cdot x + 4}{2} |
y=\frac{5\cdot x + 8}{2} |
y=\frac{x + 12}{4} |
y=\frac{-5\cdot x + 4}{4} |
y=\frac{-5\cdot x + 6}{2} |